2017
DOI: 10.1016/j.atherosclerosis.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative stimulation of atherogenesis by lipopolysaccharide and palmitic acid-rich high fat diet in low-density lipoprotein receptor-deficient mice

Abstract: Background and aims Either lipopolysaccharide (LPS) or high-fat diet (HFD) enriched with saturated fatty acid (SFA) promotes atherosclerosis. In this study, we investigated the effect of LPS in combination with SFA-rich HFD on atherosclerosis and how LPS and SFA interact to stimulate inflammatory response in vascular endothelial cells. Methods Low-density lipoprotein receptor-deficient (LDLR−/−) mice were fed low-fat diet (LFD), HFD with low palmitic acid (PA) (LP-HFD), or HFD with high PA (HP-HFD) for 20 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…When both LPS and SFA in circulation are elevated, they may act in concert to boost a strong proinflammatory response that cannot be generated by LPS or SFA alone. Indeed, our recent study supported the above notion as it showed a cooperative stimulation of atherogenesis by combining treatment of LPS with feeding SFA-rich HFD in animal models [ 7 ]. Our in vitro study also showed that palmitic acid (PA), the most abundant SFA in plasma [ 8 ], amplified LPS-triggered signaling for upregulating proinflammatory genes such as interleukin 6 (IL-6) in macrophages [ 9 ].…”
Section: Introductionmentioning
confidence: 61%
“…When both LPS and SFA in circulation are elevated, they may act in concert to boost a strong proinflammatory response that cannot be generated by LPS or SFA alone. Indeed, our recent study supported the above notion as it showed a cooperative stimulation of atherogenesis by combining treatment of LPS with feeding SFA-rich HFD in animal models [ 7 ]. Our in vitro study also showed that palmitic acid (PA), the most abundant SFA in plasma [ 8 ], amplified LPS-triggered signaling for upregulating proinflammatory genes such as interleukin 6 (IL-6) in macrophages [ 9 ].…”
Section: Introductionmentioning
confidence: 61%
“…The dose of LPS and the administration by weekly intraperitoneal injection were reported to be effective to induce atherosclerosis by the previous studies (26,52). We have also used this method in our published studies (21,22).…”
Section: Methodsmentioning
confidence: 98%
“…Therefore, it is important to elucidate the interaction between LPS and SFA on inflammation-associated diseases such as atherosclerosis and NASH. Recently, we reported that LPS and SFA cooperatively increased atherosclerosis in LDL receptordeficient (LDLR Ϫ/Ϫ ) mice, an animal model for human atherosclerosis (21). However, it remains largely unknown how the interaction between LPS and SFA affects hepatic inflammation, which is well known to contribute to atherosclerosis (48).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms by which NASH is associated with CVDs have not been fully elucidated. Our study showed that feeding HP-HFD and administration of a low dose of LPS in LDLRϪ/Ϫ mice cooperatively induced not only NASH (24) but also atherosclerosis, the major cause of CVDs (28), suggesting that the HP-HFDfed LDLRϪ/Ϫ mice treated with a low dose of LPS are a good animal model to investigate the mechanisms whereby NASH is associated with atherosclerosis.…”
Section: Introductionmentioning
confidence: 66%